Kinerja Penyuluh dan Partisipasi Petani Dalam Kegiatan Penyuluhan Pertanian Di Kecamatan Kotagajah Kabupaten Lampung Tengah - Begem Viantimala; Helvi yanfika; Abdul Mutolib; Indah Listiana; Irwan Effendi (Politeknik Negeri Lampung, 2020)
This study was aimed at analyzing the performance of agricultural instructors, participation and community satisfaction in agricultural extension activities in Kotagajah District, Central Lampung Regency. The study used a qualitative research approach. The method used in this field survey was the survey method. The results of the study provided information that the performance of agricultural extension workers as facilitators in Kotagajah District, Central Lampung Regency was good. The instructor had helped poktan (agricultural group) members to get good saprotan (agricultural equipment) and working capital, had helped members to attend training held by government / private institutions, had helped groups collaborate with government agencies or agriculture services, had helped groups collaborate with other farmer groups, and had helped groups in compiling work programs and designs for quality improvement in agriculture. Evaluation on the instructor performance has found that the agricultural instructors used material the suited the farmers need, mastered good technical and practical knowledge when delivering teaching materials, were able to manage internal and external communication with farmers, conveyed information about the importance of agricultural groups and joining the groups, responded to complaints and problems of farmers, and facilitated farmers' problems. Community participation in agricultural extension programs organized by the agricultural instructors consisted of several activities such as: being active in farmer groups, farmers joining farmer groups, farmers giving advice on the development of farmer groups, and farmers proposing extension activities. The community in general was quite satisfied with the performance of agricultural extension instructors in Kotagajah District, Central Lampung Regency. Keywords: evaluation, satisfaction, performance, participation, and agricultural extension.